The influence of member loans, own capital, total assets, and number of members on surplus in Sharia Financing Saving and Loan Cooperatives - Resmita Sakoleh; Nora Susanti; Yesmira Syamra (Review of Management, Accounting, and Business Studies, 2022)
This research aimed to analyse the influence of member loans, own capital, total assets, and number of members on Surplus in Sharia Financing Saving and Loan Cooperatives (SFSLC) in Padang City. This type of research was associative research. The sample in this research was a Sharia financing savings and loan cooperative in Padang City in 2018-2022. The sampling used a purposive sampling technique. The data analysis technique used panel data regression with EViews 8 software. The research results showed that: 1) Member loans had a positive and significant effect on the surplus of SFSLC in Padang city. 2) Own capital had a positive and significant effect on the surplus of SFSLC in Padang city. 3) Total assets did not have a positive and significant effect on the surplus of SFSLC in Padang city. 4) The number of members had a positive and significant effect on the surplus of SFSLC in Padang city. In conclusion, member loans, own capital, and number of members have a positive and significant effect on the surplus of SFSLC in Padang city.